Non pre-emptive scheduling of messages on SMTV token-passing networks - Tovar, Eduardo (2014)
Fieldbus communication networks aim to interconnect sensors, actuators and controllers within distributed computer-controlled systems. Therefore, they constitute the foundation upon which real-time applications are to be implemented. A specific class of fieldbus communication networks is based on a simplified version of token-passing protocols, where each station may transfer, at most, a single message per token visit (SMTV). In this paper, we establish an analogy between non-preemptive task scheduling in single processors and the scheduling of messages on SMTV token-passing networks. Moreover, we clearly show that concepts such as blocking and interference in non-preemptive task scheduling have their counterparts in the scheduling of messages on SMTV token-passing networks. Based on this task/message scheduling analogy, we provide pre-run-time schedulability conditions for supporting real-time messages with SMTV token-passing networks. We provide both utilisation-based and response time tests to perform the pre-run-time schedulability analysis of real-time messages on SMTV token-passing networks, considering RM/DM (rate monotonic/deadline monotonic) and EDF (earliest deadline first) priority assignment schemes